Microvascular complications and frailty can predict adverse outcomes in older patients with diabetes. Issue 4 (12th February 2021) - Sable‐Morita, Sayuri; Tanikawa, Takahisa; Satake, Shosuke; Okura, Mika; Tokuda, Haruhiko; Arai, Hidenori
Abstract : Aim: We aimed to assess whether frailty and diabetes‐related factors could predict the occurrence of adverse events in older patients with diabetes, who constitute a patient population prone to physical decline and reductions in skeletal muscle mass. Methods: This retrospective cohort study comprised 477 patients who were being managed by outpatient diabetes care, and the reductions in their muscle strength and walking speed were assessed. Patients were evaluated using the Kihon Checklist, Mini Nutritional Assessment and Mini Mental State Examination, and followed up for 1 year, during which adverse events were monitored and confirmed from past medical records and face‐to‐face interviews. Intergroup comparisons of participants with and without adverse events during the observation period were undertaken by the paired‐sample t ‐, Mann–Whitney U‐ and chi‐square tests. Multiple logistic regression analysis, adjusted for sex and age, was conducted to determine significant predictors of adverse event incidence. Results: Overall, 12.4% (n = 59; age 74.2 ± 6.2 years) of the patients experienced adverse events. We observed significant between‐group differences in the Kihon Checklist total score, walking speed, hypoglycemia episodes, nephropathy, retinopathy, and neuropathy. Microvascular complications and frailty were significant predictors of adverse event incidence (respective odds ratio [95% confidence interval]: 1.403 [1.109–1.775] per additional complication; 2.419 [1.331–4.397] for frailty; both P < 0.05). Conclusions: In this study, we found that frailty, which was assessed using the Kihon Checklist, and the number of microvascular complications predicted adverse events in older patients with diabetes and should to be assessed. Geriatr Gerontol Int 2021; 21: 359–363 .